Governing together An international review of contracts across levels of government for regional development - Charbit, Claire (OECD Regional Development Working Papers, 2017)
Contracts are a key tool for vertical co-ordination, enabling dialogue and capacity building across levels of government. They are frequently used for regional development policy in OECD and non-OECD countries. Drawing on contract theory and a variety of national experiences, this paper identifies three main types of contracts between central and subnational governments according to their objectives: i) empowerment; ii) delegation; and iii) policy-sharing contracts. The differentiation of contracts depending on their objective is based on two key factors: the maturity of decentralisation and the capacity of national and subnational governments. It is expected that with the development of subnational /central government capacities (or both), and with the increasing maturity of decentralisation, contracts can shift from one type to another. The paper concludes by suggesting enforcement mechanisms for more effective contracts across levels of government